The Russian–Ukrainian War as a Social Situation - Mykola M. SLYUSAREVSKYY; Svitlana L. CHUNIKHINA (European Journal of Interdisciplinary Studies)
This article explores the Russian–Ukrainian war as a subjectively perceived social situation, emphasizing psychological dimensions of time (present, past, and future) and their role in shaping individual and collective attitudes. Based on a February 2023 survey of 1,200 respondents in government-controlled regions of Ukraine, four groups were identified according to the subjective length of the "present"—ranging from one year to over ten years. Statistical analysis revealed that a longer subjective present correlates with less negative evaluations of the current situation, a stronger pro-Ukrainian stance, greater resistance to enemy propaganda, and more optimism about the future. Conversely, those with a shorter time perspective expressed lower trust in fellow citizens and supported harsher penalties for collaboration. The findings highlight the role of subjective time in shaping perceptions of the war’s causes, course, and possible outcomes.